How teachers' practice knowledge is used and challenged in a Learning Study using Variation Theory as a tool. Issue 3 (13th July 2015) - Ulla Runesson, Professor; Thorsten, Anja
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to discuss how teachers' practice knowledge is used as a tool in a Learning Study and how teachers' practice knowledge is challenged by using Variation Theory as a tool in the process? Design/methodology/approach – The analysis is based on data from the research process in a Learning Study. The data consists of meeting notes of ten research meetings, field notes of the research meetings and from the enactment of the lessons, video recordings of the lessons and reflective notes after and between the meetings. The analysis is qualitative and the findings are described in themes. Findings – Teachers' practice knowledge was used and challenged in different ways in the process. This is described in five themes. Teachers' practice knowledge was visible in the process since it enabled relevant questions to be addressed and subtle signals from students to be taken into account. It also ensured that the activities used were suitable for the students. The theory provided a focus on the object of learning and a language to talk about teaching and learning. It also challenged teachers' assumptions about teaching and learning and allowed them to be discussed. Originality/value – The paper addresses both teachers' practice knowledge and Variation Theory in relation to a Learning Study. It focusses on how practice knowledge of teachers can be used and challenged in the same process. The perspective is from the inside, from a teacher researcher's point of view.